Enfermedades oftalmológicas secundarias a diabetes mellitus tipo 2 en pacientes del Club de Diabéticos del Hospital Teófilo Dávila durante el segundo semestre del 2010. - Rodríguez Buenaventura, Gilberto A. (2012)
Diabetes mellitus type 2 is a disease that represents a complex metabolic disorder with multiple etiologies, which has presented an increasing incidence of people worldwide who suffer, it is now known to affect different age strata and causes complications in different organs including the eye is.